Potential of hospital corneal retrieval program in tertiary care center - Ujwala Weladi; Snehal Bonde Chaurasia (Journal of Clinical Ophthalmology and Research)
Context: In developing nations, corneal diseases are the second leading cause of blindness. Despite the effectiveness of corneal transplantation, India struggles with a substantial corneal blind population and inadequate access to quality donor corneal tissue. Addressing this gap between demand and supply is essential to combat the prevalence of corneal blindness. Aims: The aim of this study is to study the potential of hospital-based cornea retrieval program (HRCP) at tertiary care center. Subjects and Methods: A retrospective, record-based study was conducted, encompassing all hospital deaths at a tertiary center over a 2-year period from January 2016 to December 2017. Data regarding demographic profiles and causes of death due to systemic diseases were collected from the medical records. The study analyzed the number of patients from whom corneal retrieval could have been possible, after excluding those patients in whom corneal retrieval was contraindicated as per the guidelines of the National Program for Control of Blindness. Results: In 2016, a total of 6001 deaths occurred at the tertiary care center, with 2345 (39.01%) contraindicated for donor corneal retrieval. Corneas were retrieved from 42 patients, resulting in 84 corneal buttons and a retrieval rate of 0.70% of total deaths, while the potential corneal retrieval rate was 60.92%. In 2017, out of 5532 deaths, 2066 (37.38%) were contraindicated for donor corneal retrieval. Corneas were retrieved from 82 patients, yielding 164 corneal buttons and reflecting a retrieval rate of 1.48% of total deaths, with the potential corneal retrieval rate at 62.65%. Conclusions: The study highlights the potential and effectiveness of the hospital cornea retrieval program (HCRP) in a tertiary care center, with retrieval rates improving from 0.70% in 2016 to 1.48% in 2017. The gap between actual and potential retrieval rates highlights the need for better strategies. Addressing cultural barriers, superstitions, and the lack of local eye banks are crucial. Enhancing public awareness through trained counselors in hospitals and regular reorientation of medical personnel can significantly improve eye donation programs, benefiting patients awaiting corneal transplants, and reducing corneal blindness.